Working capital management, accounts receivable, and performance of Small and Medium Enterprises (SMEs) - Eton, Marus; Mwosi, Fabian; Ogwel, Bernard Patrick; Olupot, Simon Peter (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study examined how working capital managementand accounts receivables influence the performance of SMEs in Uganda and proposes policy options to address the financial and managerial challenges identified. The study provides insights into how efficient financial practices can support SME sustainability in a competitive business environment. Research Methodology: A cross-sectional research design was adopted to assess the existing conditions of working capital management and accounts receivable practices. Data were collected through a self-administered questionnaire distributed to 180 SMEs selected for the study. Inferential statistical techniques were applied during data analysis to test the research hypotheses, and several hypothesis tests were conducted to form a sound basis for interpretation and conclusion. Results: The findings indicate that improvements in working capital management significantly enhance SME performance. Similarly, better accounts receivable practices such as offering discounts and regularly reviewing credit policies—can contribute to improved financial outcomes. The results show that both working capital management and accounts receivables are significant predictors of SME performance. Conclusions: SMEs that adopt sound working capital and receivables management strategies can thrive even in challenging business environments. Effective financial management also reduces the need for borrowed capital, enabling SMEs to operate more efficiently and sustainably. Limitations: The study was geographically limited to Lira City, which may restrict the applicability of findings to broader contexts. Contribution: The study provides important guidance for SME owners and policymakers on how working capital and receivables management practices influence enterprise performance.